The temptation of forgiveness - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2018)
An accident involving the father of a boy suspected of doing drugs finds Commissario Guido Brunetti pursuing a series of false and contradictory leads before uncovering a long-standing scam and unleashing unintentional consequences.